THE IMPACT OF DIGITAL MARKETING TRAINING ON MARKETING AND SALES OF SMALL AND MEDIUM ENTERPRISES AND THE ROLE THE GOVERNMENT IN THE DIGITALIZATION PROCESS - Husna, Faizah Khotimatul; Tamtama, Noviadry Nur; Nurrokhmini, Alfiati (FE Program Studi Manajemen, 2026)
The urgency of this research lies in the importance of ensuring that digital marketing training programs are truly effective in increasing the competitiveness of MSMEs. Although digitalization has great potential to expand market reach and improve business efficiency, many MSMEs still face obstacles such as low digital literacy, limited resources, and restricted access to quality training. This research aims to analyze the extent to which digital marketing training contributes to improving the marketing and sales performance of MSMEs.The results of this research conclude that digital marketing training has a significant impact, both directly and indirectly, on enhancing the marketing and sales capabilities of MSMEs. This shows that the more intensive and higher-quality digital training received, the greater the competitiveness of MSMEs in marketing their products. However, the digital transformation of MSMEs cannot rely solely on individual initiatives; the government’s role as a facilitator is also crucial